PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA DI SEKOLAH DASAR - Dudwina Dia; Rahma Ashari Hamzah (Jurnal Pendidikan Nusantara, 2025)
This study aims to systematically examine the development of Indonesian language teaching materials using the Systematic Literature Review (SLR) method, analyzing 14 articles. The results of the study indicate five main trends in the development of Indonesian language teaching materials: the use of digital technology such as Augmented Reality, Flipbooks, electronic modules, and animated videos; the integration of character education; the integration of local wisdom; the selection of development models such as ADDIE and Borg & Gall; and the use of children's literature to strengthen literacy. Furthermore, dominant literacy issues were identified, such as a low understanding of the intrinsic elements of texts and a lack of variety in teaching materials used by teachers. This study confirms that the development of innovative contextual, and technology-based teaching materials is an urgent need to improve the quality of Indonesian language learning and support the achievement of the Independent Curriculum. These findings are expected to serve as a reference for researchers and educators in developing teaching materials that are more relevant to the needs and characteristics of students.